Estimation of vitamin E level and its relation to lipid profile in patients with type II Diabetes Mellitus - Al-Ramadhan, Amani N.; Mahmood*, Ihsan S.; Al-Naama, Lamia M.; Al-Naama, Lamia M.; Strak, Sakis K. (AL-Kindy College Medical Journal, 2015)
Background: Type 2 diabetes mellitus (T2DM) is considered a global disease as it affects over 150 million people worldwide, a number that is supposed to be doubled by 2025. High glucose levels, in vitro, appear to raise the extent of LDL oxidation, and glycated LDL is more prone to oxidative modification.Objective: To investigate the relationship between serum level of vitamin E and lipid profile in patients with type II DM.Methods: This study involved 28 patients suffering from type II DM diagnosed 1-4 years ago and with age ranged from 17 -60 years old, with different residence around Basra ; In addition to 56 apparently healthy persons matched in age and sex to the patients as a control group. The medical histories were taken and General examinations were done to them with measurement of their height and weight. Four milliliters of venous blood was drawn from each patient and control to measure TG, TC, VLDL, HDL, LDL, HbA1C and Vitamin E and the results were used to assess the presence of any association between Vit E levels and lipid profile.Results: The mean levels for patients and controls of TG were (157.1± 24.9 and 119.8 ± 29.0) mg/dl, of TC were (204.0 ± 43.2 and 168.0 ± 31.5) mg/dl, of VLDL was (31.5 ± 5.0 and 24.2 ± 5.9) mg/dl, of LDL was (129.6 ± 42.8 and 97.6 ± 30.8) mg/dl, of HDL was (42.9 ± 10.2 ± 46.0 ± 9.0) Mg /dl, of HbA1C were (9.4 ± 3.0 and 5.0 ± 0.7) % and of vitamin E were (3.7 ± 1.3 and 6.8 ± 2.0) mg/dl, respectively.There was a significant difference between all the above measured parameters, except of HDL, between cases and controls. Also there was a significant association between DM type II and low level of vitamin E. there was a significant negative correlations between vitamin E and TG, TC, LDL, VLDL but not HDL, even after adjustment for age, sex and BMI.Conclusion: Diabetes mellitus type II has a significant effect on vitamin E which is an important guard against dyslipidemias, one the major causes of diabetes vascular complications